PEMODELAN NOISE MAPPING DAN ANALISIS WAKTU PEMAPARAN MAKSIMUM PADA AREA GRAVING DOCK - Restu hikmah ayu murti; Alfiana Sabela (Prosiding ESEC, 2023)
Graving dock is a ship repair and maintenance site that is underground or called a dug / pool dock so that the activity of ship repair takes place below ground level. In its operational activities, noise is generated such as the Sandblasting process which uses a compressor machine when spraying silica sand on a steel plate with high pressure. Continuous repair activities have the potential to affect the health and comfort of workers. The purpose of this study is to analyze the value of noise generated from ship repair work in the dock graving area and compare it with Permenaker No.5 of 2018 as the threshold value of noise level, determine the maximum time of noise exposure allowed based on the results of the study, and noise control efforts. The research method is by measuring the noise level with 16 measurement points using SLM equipment and calculating the exposure time with the NIOSH equation. The results showed the lowest noise level was 81 dB and the highest was 103 dB. Based on the calculation using the NIOSH equation from 16 points of the noise mapping method results, there 1 points that show inposure time above the NIOSH recommended standard. The planned noise control measures are engineering, administrative, and PPE control.